Early Emotional Symptoms Predicting Carotid Atherosclerosis in Youth: Results From a Birth Cohort in Latin America. Issue 2 (22nd January 2019) - Belem da Silva, Cristiano Tschiedel; Hoffmann, Maurício Scopel; Sant′Anna, Roberto Tofani; Wehrmeister, Fernando César; Gonçalves, Helen; Oliveira, Isabel O.; Oliveira, Paula Duarte; Vargas da Silva, Antônio Marcos; Kieling, Christian; Manfro, Gisele Gus; Menezes, Ana M. B.
Abstract : Background: Emotional disorders are risk factors for atherosclerosis and consequent cardiovascular disease. However, it is not clear whether emotional symptoms (ESs) have direct effects on cardiovascular disease. The aim of the present study is to investigate the effects of early ESs on carotid atherosclerosis in young adults. Methods and Results: We tested the association between expression of ESs at 11 and 15 years of age and carotid intima‐media thickness at 18 years of age in the 1993 Pelotas Birth Cohort (N=5249, n=4336 with complete mental health data). ESs were assessed using the Strengths and Difficulties Questionnaire. Propensity score weighting procedure was run using generalized boosted regression model to adjust for potential confounding between exposure and outcome. We also tested whether traditional cardiovascular risk factors could mediate this relationship. Adjusted high expression of ESs, both at 11 and 15 years of age, led to mean increases in carotid intima‐media thickness of 1.84 and 2.58 μm, respectively, at 18 years of age (both P <0.001). Longitudinal effects of ESs on atherosclerosis were direct and not significantly mediated by traditional cardiovascular risk factors. Male sex at age 15 years significantly enhanced the effects of ESs on carotid intima‐media thickness at age 18 years ( P <0.001 for interaction): although high expression of ESs led to mean increases of 1.14 μm in females ( P <0.05), it led to mean increases of 5.83 μm in males ( P <0.001). Conclusions: In this large birth cohort, expression of ESs in adolescence was longitudinally associated with a higher carotid intima‐media thickness in young adults. The association is direct and not mediated by traditional cardiovascular risk factors. Interactions by sex might have important implications for designing future interventions.